Pemahaman Pembangunan Doktrin Kekudusan Allah bagi Mahasiswa Teologi - Agus Prayitno (Sekolah Tinggi Teologi Imauel Pacet, 2020)
An understanding of the doctrine of holiness in particular for College Theology students is still a confusion, due to a less clear definition of the meaning of holiness among students. For this discussion, the writer emphasizes more on the meaning of holiness for believers and specifically for theological high school students who will be incited as potential leaders. And that should be an example for those they lead. Some events of the leaders have not become a guarantee to be exemplary in holiness, even sometimes it is better for laypeople to protect holiness. Therefore in this writing theology students as prospective leaders must be good examples in terms of holiness. Because it will be seen and emulated for the people they lead.Abstrak : Pemahaman akan doktrin kekudusan secara khusus bagi mahasiswa Sekolah Tinggi Teologi masih menjadi suatu kerancuan, akibat definisi yang kurang jelas dari makna kekudusan dikalangan mahasiswa. Untuk dalam pembahasan ini penulis lebih menekankan apa sebenarnya makna kekudusan bagi umat percaya dan secara khusus bagi mahasiswa sekolah tinggi teologi yang akan duduka sebagai calon-calon pemimpin. Dan yang seharusnya menjadi teladan bagi yang dipimpinnya. Beberapa peristiwa para pemimpin belum menjadi jaminan untuk menjadi keteladanan dalam kekudusan, bahkan terkadang lebih baik orang awam untuk menjada kekudusan. Karena itu dalam penulisan ini para mahasiswa